The feeding value of wheat and high moisture sorghum grain fed singly and in combination to finishing steers - D. Axe; K. Bolsen; R. Lee; George M. Herron (Kansas Agricultural Experiment Station Research Reports, 1986)
Wheat and high moisture sorghum grain were fed singly and in two combinations in a 121-day feedlot trial at the Garden City Branch Experiment Station. Feed efficiency improved with increasing proportions of wheat in the ration. However, rates of gain were similar for the three wheat-containing rations. Results showed that at least 33% sorghum grain can be substituted for wheat in finishing rations with little influence on performance. The combination rations produced rates of gain that were above predicted values, indicating positive associative effects.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Wheat; Sorghum grain; Finishing steers